With Awareness Comes Competency: The Five Awarenesses of Teaching as a Framework for Understanding Teacher Social-Emotional Competency and Well-being. Issue 7 (2nd October 2020) - Rodriguez, Vanessa; Lynneth Solis, S.; Mascio, Bryan; Kiely Gouley, Kathleen; Jennings, Patricia A.; Brotman, Laurie M.
ABSTRACT: Research Findings: Developing students' social and emotional skills positively affects their academic success. The Prosocial Classroom model (PCM) highlights the importance of teacher's social-emotional competency (SEC) and well-being. The current research extends the PCM by using the Five Awarenesses of Teaching Framework (The Framework) to understand teacher SEC through a developmental lens. We discuss how the Framework can inform and be informed by our understanding of Early Care and Education (ECE) teachers' SEC. Eighteen ECE teachers participated in cognitive interviews and a deductive thematic analysis was used to categorize teachers' interview data according to The Framework. Three key themes were identified: 1) The Framework described cognitive capacities relevant to ECE teacher SEC consistent with other teacher populations; 2) there was an underlying conflict between teachers' keen awareness of student social-emotional learning (SEL) and an active suppression of their own social and emotional well-being; and 3) the impact and importance of race, ethnicity, and family engagement. Practice or Policy : Findings reveal that ECE teachers' SEC and well-being can be described using The Framework. Additionally, the suppression of ECE teacher emotional needs and the importance of family engagement suggest important avenues for improving our understanding of ECE SEC and well-being.